Evaluation Of Turbidity Measuring Using IoT Based Sensors - Tay, Ying Keat (Universiti Sains Malaysia, 2022)
Water serves many important roles in our daily life. Thus, it is essential to monitor our water quality. IoT water quality monitoring system is one of the most popular method to track the water quality as it offers real-time monitoring and accessibility of data through cloud. To ensure the system delivers its function, the accuracy of the sensors is the key element that we must focus on. In this study, the turbidity sensor measuring capability is evaluated. Owing to new data attained, the formula provided by the manufacturer yielded poor accuracy and a new voltage-turbidity conversion formula is needed. The turbidity sensor will be tested with solution with known turbidity value and a new formula will be derived. After that, the turbidity sensor with the new formulation will be put under various turbidity measurements using oil emulsion, dye solution, protein emulsion, calcium carbonate solution and pure water to validate its performance. Besides that, the repetitive turbidity measurement on calcium carbonate solution and water is successfully carried out. Time-based turbidity measurement on calcium carbonate solution, oil emulsion, dye solution and protein emulsion are carried out.